2021
DOI: 10.1097/phh.0000000000001329
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Linkage Between Accreditation Outcomes and Public Health Emergency Preparedness and Response

Abstract: Public health emergency preparedness is a critical health department function. The national public health accreditation program may enhance public health preparedness by building the capabilities and overall capacity of health departments and also by improving capabilities specific to preparedness. This study presents findings from a survey sent to health departments 1 year after achieving accreditation, with a focus on accreditation outcomes related to public health preparedness. Between April 2014 and Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Lastly, more than two third of respondents (68.7%) reported that accreditation also boosted the health department's use of evidence-based methods. These findings provide evidence that, in addition to improving overall health department capacities, accreditation also supports the national guidelines, criteria, and activities identified as critical for developing and maintaining preparedness capability within the governmental public health system [36].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Lastly, more than two third of respondents (68.7%) reported that accreditation also boosted the health department's use of evidence-based methods. These findings provide evidence that, in addition to improving overall health department capacities, accreditation also supports the national guidelines, criteria, and activities identified as critical for developing and maintaining preparedness capability within the governmental public health system [36].…”
Section: Discussionsupporting
confidence: 53%
“…However, the actual change takes time to be built into the organization and become a habit. Kennedy et al (2022) investigated the results of preparedness-related accreditation that may impact emergency preparedness response and recovery capabilities in the United States. The research used data collected by the National Opinion Research Center based on a poll of health departments after a year of accreditation.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from this analysis illuminate how the public health department accreditation program has improved outcomes for LHDs, particularly small LHDs, in strengthening staff competencies, capacity to provide high-quality services, use of evidence-based practices, and relationships with partners. These benefits may support the capacity of health departments to prepare for and respond to emergencies and threats, including COVID-19 19,20. LHDs have been central to the nation's response to the COVID-19 pandemic, and ongoing support is vital for strengthening the capacity of the public health system to respond to future emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits may support the capacity of health departments to prepare for and respond to emergencies and threats, including COVID-19. 19,20 LHDs have been central to the nation's response to the COVID-19 pandemic, and ongoing support is vital for strengthening the capacity of the public health system to respond to future emergencies. There is an ongoing need in the United States to ensure that the public health system has the capacity to respond to emergencies and threats, prevent chronic disease, and improve population health.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Regarding public health accreditation, PHNCI's accomplishments include incorporating innovation into public health accreditation and developing resources that link innovation and transformation to accreditation. Accreditation has been associated with positive outcomes in participating health departments21 and may also strengthen key areas related to public health emergency preparedness and response 22. Identifying opportunities to strengthen the accreditation program by incorporating innovative ideas may serve to strengthen the public health field as a whole and enhance the capacity of health departments to address emerging and ongoing public health threats and challenges.…”
Section: Discussionmentioning
confidence: 99%